MEMAHAMI KAIDAH USHULIYAH LUGHAWIYAH PERSPEKTIF TIORI AHNAF - Faiz Zainudin; Arif Hariyanto (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2020)
The problem of innovation is a trigger factor in the religious disharmony, claims of truth occurs only on one side, and regard the other with false accusations and even accused as infidels. Heresy at the time still not Resolved, justruh become even more tapered and-so. They had perverted heretical propaganda through mass media like radio, fatwa commission, salebaran, and other writings, such accusations Surprisingly more precisely lead to the Expert Sunnah Wal Jama'ah. For that, it should be with the polemics of this kind needs be no specific response to concerns relating to issues that have been merasahkan and disrupt the comfort and harmony of religions, especially Islam in terms of legal analysis. The goal is that these problems can be solved by the decision of the best and can provide solutions that can diajalankan by the public, and can eliminate the unilateral truth of the allegations. Furthermore, to provide the best solution on the claims of heresy heresy, in society, the author gives an explanation which is very comprehensive in answering the issues around innovation with the proposition that qhat'i berlandasankan and accountable, in the form of al-Quran and Hadith-Hadith sahih, but it is also the author gives a real understanding of what it is heresy and Islamic attitudes in response to this polemic. Because the moment is now so easy to claim someone on charges of heresy that ultimately leads to infidelity. The design of the study is a research library research (literature study) using the method of qualitative analysis with deductive and descriptive way of thinking. The results of this study, is to assert that not all innovations are prohibited, senayampang heresy has qhat'i cornerstone arguments. Even the heretics also be recommended by the Sunnah of the Prophet. In addition to the understanding of the hadith also straighten often used as a reference by those who say all heresies heresy, as well as provide an understanding of how to determine the proper position on the hadith, as well as introducing a method to determine the hadith in order to understand haidits with true understanding. Based on the results of this study, recommended for groups who claim to truth as Islamic fundamentalist and liberal Islam should not only understand the hadith of the literal aspect dhahirnya alone or, if a hadith is understood from the aspects dhahirnya will certainly experience a fatal error kerana pemahamn like it was just owned by someone who have an interest or based on lust.